2020
DOI: 10.1111/jfpe.13447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of thermosonication and pasteurization on total phenolic contents, total flavonoid contents, antioxidant activity, and vitamin C levels of elephant apple (Dillenia indica) juice

Abstract: The present work evaluated the influence of different thermosonication conditions on the quality improvement of elephant apple (Dillenia indica) juice. The juice was processed under thermosonication at different temperatures (30–50°C) for different time periods (15–60 min). The results of sonication treatments were compared with fresh and thermally treated juices. The objectives of the research work were to determine the effect of thermosonication on the quality attributes such as pH, titratable acidity (TA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
5
22
0
Order By: Relevance
“…Iodine titration method was used for the estimation of ascorbic acid levels in tangor juices (Nayak, Basumatary, et al, 2020). Ascorbic acid levels in juices were presented as mg of ascorbic acid per 100 ml of juice.…”
Section: Methodsmentioning
confidence: 99%
“…Iodine titration method was used for the estimation of ascorbic acid levels in tangor juices (Nayak, Basumatary, et al, 2020). Ascorbic acid levels in juices were presented as mg of ascorbic acid per 100 ml of juice.…”
Section: Methodsmentioning
confidence: 99%
“…FCCD ( α = 1) offers higher quality predictions between the design ranges with minimal experimental runs (Sasikumar et al, 2019). For predictive modeling—various equation models were considered for the fitness of experimental data (Nayak et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of flavonoid content in Cavendish banana juice was initially 0.1691 mg QE/ g sample. these compounds are sensitive to heat and will be degraded at temperature over 60 ℃ (Nayak et al, 2020). The results of statistical analysis showed that interaction of pasteurization temperature and time had a significant effect on the total flavonoid content in Cavendish banana juice.…”
Section: Total Flavonoid Contentmentioning
confidence: 99%